Tonal distributions in the music of the renaissance (2015)
In this study we use the technique of note counting, tonal hierarchies and the algorithm to find tones to quantitatively assess how much the Renaissance musical language and subsequent tonal language resemble. The results show that there is a great correspondence between the tonal distributions of both languages and between them and the tonal hierarchies found by Krumhansl and Kessler (1982). This suggests that the differences are smaller than what is usually considered and that, in the Renaissance, there is a hierarchy of tones similar to that of tonalism. On the other hand, some problematic cases show that modal language favors tonal ambiguity. Finally, empirical evidence is provided to the notion that, in the Renaissance, the system tends, progressively over time, to two poles: the major hue and the minor hue.